2013
DOI: 10.3402/tellusb.v65i0.19054
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of clouds and precipitation depending on different relationships between aerosol and cloud droplet spectral dispersion

Abstract: The aerosol effects on clouds and precipitation in deep convective cloud systems are investigated using the Weather Research and Forecast (WRF) model with the Morrison two-moment bulk microphysics scheme. Considering positive or negative relationships between the cloud droplet number concentration (Nc) and spectral dispersion (ε), a suite of sensitivity experiments are performed using an initial sounding data of the deep convective cloud system on 31 March 2005 in Beijing under either a maritime (ȁ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Table 6 shows the global, Northern Hemisphere, and Southern Hemisphere annual mean changes of liquid water path ( LWP), cloud-top effective radius ( REL), shortwave cloud radiative forcing ( SWCF), longwave cloud radiative forcing ( LWCF), and total cloud radiative forcing (AIF) induced by aerosols in News. With an increase in anthropogenic aerosols, the LWP can be increased by the decreased autoconversion rate to form raindrops, and additionally the REL can be reduced significantly due to the enhanced activation of aerosols to cloud droplets (Xie et al, 2013). Due to the increased LWP and the decreased REL, the SWCF and LWCF can be increased by anthropogenic aerosols, and the total cloud radiative forcing (SWCF+LWCF) can also be increased, where the aerosol-induced SWCF is dominated for changes in the total cloud radiative forcing.…”
Section: Evaluation Of Aif Including the Dispersion Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 shows the global, Northern Hemisphere, and Southern Hemisphere annual mean changes of liquid water path ( LWP), cloud-top effective radius ( REL), shortwave cloud radiative forcing ( SWCF), longwave cloud radiative forcing ( LWCF), and total cloud radiative forcing (AIF) induced by aerosols in News. With an increase in anthropogenic aerosols, the LWP can be increased by the decreased autoconversion rate to form raindrops, and additionally the REL can be reduced significantly due to the enhanced activation of aerosols to cloud droplets (Xie et al, 2013). Due to the increased LWP and the decreased REL, the SWCF and LWCF can be increased by anthropogenic aerosols, and the total cloud radiative forcing (SWCF+LWCF) can also be increased, where the aerosol-induced SWCF is dominated for changes in the total cloud radiative forcing.…”
Section: Evaluation Of Aif Including the Dispersion Effectmentioning
confidence: 99%
“…Several empirical expressions have been proposed to represent ε in terms of the droplet number concentration (reviewed by Xie et al, 2013). Here, three commonly used expressions are used to investigate the dispersion effect.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the N c -ε relationship (positive or negative change of ε with N c ) influences the autoconversion process (i.e conversion of cloud droplets to raindrops), and therefore affects the response of ground precipitation to a change in aerosols concentration. Xie et al (2013) suggested that for a positive N c -ε relationship, the large-sized rain drops at high aerosol concentrations enhance the efficiency of the surface precipitation. The diversity of schemes for the N c -ε relationship (as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the impact of aerosol loading on ε should be well understood for enabling suitable use of climate models in quantifying the impact of aerosol loading on the droplet size distribution, effective radius, and clouds' reflectivity. Xie et al (2013) studied four types of parameterizations for treating the relationship between N c and ε. They implemented these schemes into the Weather Research and Forecasting (WRF) model, aimed at studying the effects of aerosol on cloud microphysics and ground precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The effective cloud droplet radius is related to the volume radius (r 3 ) by a ratio (b, r e = br 3 ), which in turn is a function of the relative dispersion of the cloud droplet spectrum (e) (Pontikis and Hicks 1992;Martin et al 1994;Daum 2000, 2002).This indicates that the relative dispersion therefore plays a key role in determining the cloud optical properties because of its intrinsic relationship with effective cloud droplet radius. Moreover, e also affects the automatic conversion rate from cloud water into rain water (Liu et al 2006a;Xie et al 2013), and consequently alters the lifetime of clouds. It is thus evident that the relative dispersion of cloud droplet spectrum (e) is a highly important cloud microphysical parameter.…”
Section: Introductionmentioning
confidence: 99%